Pengaruh Massage Counter Pressure Terhadap Lama Kala 1 Fase Aktif Persalinan Normal - Yussie Ater Merry; Mardiani Bebasari; Olana Rahma Ridanta (Poltekkes Kemenkes Denpasar, 2021)
The smoothness of labor can be influenced by various factors, including psychological factors, namely anxiety and pain during uterine contractions. Physiological pain and maternal anxiety that are not handled properly can lead to prolonged labor, asphyxia and lead to maternal and infant mortality. Massage counter pressure is a non-pharmacological method used to treat pain and anxiety during childbirth. The aim of the study was to determine the effect of counter pressure massage on the duration of the 1 active phase of normal labor. This research method is pre experiment with static group comparison design. Research conducted in PMB Halimatun Sakdiah, Amd.Keb and Midwife Practice Together Kurao Padang City on 23 January – 01 March 2018. The Samples were taken by Accidental Sampling on the active maternal mother of 1 phase. The number of sample are 32 people, 16 in the control group and 16 in the treatment group. Statistical test using univariate and bivariate data analysis with Unpaired T Test. The results of the research obtained the average duration of 1 active phase in the the treatment group 141.25 minutesand control group 195.94 minutes then the average the difference of the mean was 54.688 minutes. From the statistical test obtained p value = 0.039 indicate the influence of massage counter pressure on the duration of stage1st active phase of normal labor. The conclusion of this research massage counter pressure technique proved able to accerelate long time of 1st active phase of normal labor. Expected massage counter pressure will be an alternative intervention in acelerating the stage of 1st active phase of normal labor.